Pengaruh Biaya Operasional dan Pendapatan Operasional (BOPO) dan Non Performing Financing (NPF) Terhadap Return On Asset (ROA) di Bank Umum Syariah Indonesia Tahun 2015 - 2019 - Malik, Riduan (JYRS: Journal of Youth Research and Studies, 2021)
The purpose of this study was to determine the effect of ROA and NPF on UMKM financing at BPRS in Indonesi 2014-2018. This reseach uses quantitative reseach. This study uses secondary data sources. The analisis used is the calssical assumption test and hypothesis testing using the F, t and R2 statistical tests. The results of this study indicate that the Return On Asset (ROA) is know to have a probability value of 0,4611 > 0.05, so that ROA is indicated as having no effect significant toward UMKM financing distribution, while for Non Performing Financing (NPF) it is known that the probability value of 0,0000 <0,05, so that NPF has a positive and significant effect on the distribution of UMKM financing.